Structured Sentencing Algorithm for Ukraine - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (Elsevier, 2025)
This article presents the development of a structured sentencing algorithm for Ukraine that seeks to reconcile national principles of individualization with European standards of proportionality, while incorporating the autonomous interpretation of Article 7 of the European Convention on Human Rights (ECHR). It identifies the limitations of applying a general sentencing formula to specialized liability regimes, including martial law, corruption offenses, traffic offenses under intoxication, military offenses, domestic violence, genocide, and crimes against humanity. A refined sentencing formula is proposed, incorporating corrective mechanisms and exceptions, informed by the conceptual principles of the Draft New Criminal Code of Ukraine. The article also emphasizes the importance of judicial reasoning, transparency, and predictability while safeguarding proportionality in high-risk legal contexts. У цій статті представлено розробку структурованого алгоритму призначення покарання для України, який має на меті узгодити національні принципи індивідуалізації з європейськими стандартами пропорційності, одночасно враховуючи автономне тлумачення статті 7 Європейської конвенції з прав людини (ЄКПЛ). У ній визначено обмеження застосування загальної формули призначення покарання до спеціалізованих режимів відповідальності, включаючи воєнний стан, корупційні правопорушення, правопорушення, вчинені в стані сп'яніння, військові злочини, домашнє насильство, геноцид та злочини проти людяності. Запропоновано вдосконалену формулу призначення покарання, що включає коригувальні механізми та винятки, що базується на концептуальних принципах проекту нового Кримінального кодексу України. У статті також наголошується на важливості судового обґрунтування, прозорості та передбачуваності, одночасно забезпечуючи пропорційність у високоризикованих правових контекстах.
Tuliakov V. Structured Sentencing Algorithm for Ukraine // V. Tuliakov. - (November 22, 2025). - 32 p. - Режим доступу: Available at SSRN: https://ssrn.com/abstract=5785502 ; http://dx.doi.org/10.2139/ssrn.5785502 ; Publication date: 26 Nov. 2025
Keywords: Sentencing; Proportionality; Maïs Case; Special Liability Regimes; Article 7 ECHR; Military Offenses; Corruption; Autonomous Interpretation; Винесення вироку; пропорційність; справа Маїса; режими спеціальної відповідальності; стаття 7 ЄКПЛ; військові злочини; корупція; автономне тлумачення